Penguatan Politik Islam Turki oleh Presiden Erdogan melalui Pengubahan Status Hagia Sophia - Restuning Tyas, Tri; Albayumi, Fuad; Dody Molasy, Honest (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2022)
This article begins with the controversy that arose after President Erdogan decided to reopen the Hagia Sophia as a mosque after 86 years of being a museum. Hagia Sophia is a building that is also a symbol and witness to the reign shifting that have occurred in Turkey. This article will discuss the reasons behind the decision that has been taken by President Erdogan. To answer this question, this paper uses literature studies and other secondary data. Furthermore, the data that has been obtained will be analyzed using qualitative descriptive analysis techniques. The results of the research indicate that President Erdogan's policies which have pros and cons, are one of the tools to realize several political agendas. The agendas are (1) the consolidation of Turkey's domestic politics, as well as (2) strengthening Turkish Islamic politics in the international arena.